Ethanol detection using composite based on reduced graphene oxide and CuO hierarchical structure under wet atmosphere - Modenes-Junior, Marco A. [UNESP]; Zito, Cecilia A. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2019)
Semiconductor metal oxides have been used for detecting volatile organic compounds (VOCs). However, these materials present a poor performance in humidity. Here, we report the effect of reduced graphene oxide (RGO) on the ethanol-sensing of CuO under dry and in the relative humidity range of 36–90%. For this purpose, RGO-CuO composites and CuO were synthesized by a one-step microwave-assisted synthesis. The VOCs sensing were performed at the range of 150–350 °C to acetone, benzene, ethanol, methanol, and m-xylene. The RGO-CuO composites exhibited enhanced ethanol sensing when compared with pure CuO at the optimal operating temperature of 250 °C. In addition, the optimal RGO content resulted in an enhanced selectivity and high sensitivity compared to pure CuO. The enhanced ethanol sensing performance of RGO-CuO was attributed to the RGO/CuO heterojunction. Thus, the combination of RGO and p-type CuO semiconductor can be a promising for VOCs detection under wet conditions.
Keywords: Graphene-based composite; p-type SMO; Volatile organic compounds; Water cross-interference